Collected Works - Ockeghem, Johannes c. 1410-1497; Plamenac, Dragan 1895-1983; Wexler, Richard (USA Galaxy Music Corporation, 1959)
Scholarly edition of the great Franco-Flemish master of the fifteenth century.